KEPEMIMPINAN KYAI DALAM MENINGKATKAN MUTU PENDIDIKAN PESANTREN - M. Shodiq (el-hikmah, 2011)
Advanced level of a private boarding school is very dependent on their kyai (religious scholars), especially by the expertise and the depth of religious knowledge, authority and charisma of religious scholars as well as skill in managing the boarding (pesantren). The Leadership of Kyai In Enhancing The Quality Of Education In Boarding School in this study divided the two include: (1) The Leadership of Kyai in the boarding school that is as "agent of change" in the community who was instrumental in a process of social change, (2) The Leadership of Kyai in learning that is as planner , implementers and evaluators of all activities conducted at the seminary.